Radiographic measurements related with the cardiac size in young female Bergamasca sheep - Babicsak, Viviam R. [UNESP]; Alves, Lidiane S. [UNESP]; Tsunemi, Miriam H. [UNESP]; Vulcano, Luiz C. [UNESP] (FapUNIFESP (SciELO), 2017)
In thoracic radiographic examination, routinely used in cases which cardiac evaluation is indicated, quantitative assessment of the heart is a useful role to be used in combination with subjective analysis. Numerous studies about objective assessment of the cardiac size have been performed in several species, including sheep; however, there is scarce information regarding cardiac parameters of young Bergamasca sheep. Therefore, the purpose of this study was to determine the average results and suggest the range of expected normal values for parameters related to the heart size of young female Bergamasca sheep by radiographic evaluation. Fifteen healty 8 months-old female Bergamasca sheep (mean weight: 41.13±4.71kg) were submitted to right lateral recumbency thoracic radiography. The length of the fourth and third to fifth thoracic vertebrae, cardiac height and width, vertebral heart size, cardiophrenic contact, caudal vena cava height, aorta caliber and tracheal angle were measured and the mean results found were, respectively: 2.46±0.11cm (95% CI 2.41-2.52), 7.53±0.30cm (95% CI 7.38-7.68), 13.83±0.57cm, (95% CI 13.54-14.12), 8.99±0.37cm (8.80-9.17), 8.99±0.27 vertebrae (95% 8.85-9.13), 4.55±0.70cm (95% CI 4.19-4.90), 1.88±0.19cm (95% CI 1.79-1.97), 2.05±0.11cm (95% CI 2.00-2.11) and 14.36±2.73° (95% CI 12.98-15.75). Cardiac height and width and the sum of these parameters were compared to the length of third to fifth thoracic vertebrae, resulting in the respective mean values: 1.84±0.08 (95% IC 1.80-1.88), 1.20±0.05 (1.17- 1.22) and 3.04±0.11 (95% IC 2.98-3.09). Ratios of cardiophrenic contact to cardiac height and caudal vena cava height to length of fourth thoracic vertebra were also evaluated and the mean values obtained were 0.33±0.05 (95% IC 0.30-0.35) and 0.76±0.08 (95% IC 0.72-0.81), respectively. Authors suggest that the values available in this study may be used as reference for normal heart size in young female Bergamasca sheep and as basis for further studies.
Keywords: Cardiology; Heart; Morphometry; Radiography; Radiology; Sheep